STRATEGI POLITIK DALAM PENGENTASAN DESA TERTINGGAL - Rusdiono, Rusdiono; Patriani , ⁠Ira; Padilah, Ahirul Habib; Yursa, Dadi Sunarya Usfa; Alamri, Annisa Rizqa; Apriyani, Eka (Universitas Hamzanwadi, 2023)
The village development program run by the government in reducing poverty in rural areas, in its implementation, especially for all parties, is still in doubt. The village categories based on the Highly Underdeveloped Village Index (IDM) and Disadvantaged Villages show a correlation with the condition of the poor population in these village categories. For this reason, demands for a joint political strategy between the government and the community are urgently needed, related to strengthening decentralization, changing the role of the local bureaucracy and building community participation in efforts to alleviate underdeveloped villages or poor villages in order to contribute to reducing poverty in rural areas. This study uses a qualitative research method with a descriptive approach with a purposeito make a charmisystematically,ifactual andiaccurate factsiand population traitsior certain areas. The results of the research show that on the Village Government service side it is still not on target, programs that should be for the poor are also enjoyed by the rich. So that the poor do not develop and do not increase their standard of living, this causes the village to still be in the category of underdeveloped villages, even very underdeveloped.